The Influencing Factors of Men Consumers Behaviour Towards facial Wash Skin Care Product - Laksono, Doni; Purwanegara, Mustika Sufiati (Journal of Business and Management, 2014)
This study focuses on male consumersÃ¢â‚¬â„¢ behavior towards men facial wash products, consumersÃ¢â‚¬â„¢ values, and the influencing factors of it. The current globalization occurs and impacts to menÃ¢â‚¬â„¢s behavior in consuming beauty products. The masculinity mindset has moved from Ã¢â‚¬Å“men are seen by what they produceÃ¢â‚¬Â to Ã¢â‚¬Å“men are seen by what they consumeÃ¢â‚¬Â. The questionnaire which contains demographic, consumersÃ¢â‚¬â„¢ value, loyalty, influencing external factors was conducted by adapting from previous research journal related to menÃ¢â‚¬â„¢s consumption behavior. The questionnaires were distributed for men who use facial wash product in Bandung and Jakarta with 250 respondents in age range between 16 to 30 years old. Data were analyzed by using Ms. Excel and IBM SPSS 19 for Windows through descriptive analysis, cross tabulation, linear regression analysis, conjoint analysis, discriminant analysis, and factor analysis. The data showed that there is a relationship between the influencing external factors and consumersÃ¢â‚¬â„¢ value towards male consumers in purchasing facial wash products.Keywords: Men facial wash, menÃ¢â‚¬â„¢s consumption behavior, skincare